PSYCHOEDUCATION ON THE IMPORTANCE OF DIGITAL PARENTING FOR GENERATION Z - Rohmah, Auliyah; Tsani , Nur Fajriatus; Rahman , Mirza Asyraqi; Maulidhah , Chafi Rozyi Putri; Maryam , Effy Wardati; Laili , Nurfi (Antis-publisher, 2025)
Objective: This study aims to evaluate the effectiveness of psychoeducation on digital parenting in enhancing parents' understanding of appropriate parenting strategies for Generation Z in the digital age. Method: The research involved community service activities, providing psychoeducation sessions to 30 guardians or parents of students. A paired sample t-test was conducted to measure changes in understanding, comparing pre-test and post-test scores. Results: The findings reveal a significant improvement in parents' understanding of digital parenting, with the average score increasing from 35.767 (pre-test) to 39.233 (post-test). This demonstrates that psychoeducation positively impacts parents' ability to adopt effective digital parenting practices. Novelty: This study highlights the importance of targeted psychoeducational interventions in addressing the challenges faced by Generation Z’s parents in managing the rapid advancement of digital technology. It provides empirical evidence supporting the role of psychoeducation as a practical tool to improve parental guidance in a digitally-driven environment.